2003
DOI: 10.1110/ps.03256803
|View full text |Cite
|
Sign up to set email alerts
|

Solution structure and function of an essential CMP kinase of Streptococcus pneumoniae

Abstract: Streptococcus pneumoniae is a major human pathogen that causes high mortality and morbidity and has developed resistance to many antibiotics. We show that the gene product from SP1603, identified from S. pneumoniae TIGR4, is a CMP kinase that is essential for bacterial growth. It represents an attractive drug target for the development of a novel antibiotic to overcome the problems of drug resistance development for this organism. Here we describe the three-dimensional solution structure of the S. pneumoniae C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 38 publications
1
13
0
1
Order By: Relevance
“…The cmK gene encodes cytidine kinase that catalyzes the phosphoryl transfer from ATP to cytidine monophosphokinase (CMP) and deoxycytidine monophosphokinase (dCMP), resulting in the formation of nucleotide diphosphates in cellular nucleic acid synthesis. A previous study found that cmK is an essential CMP kinase for bacterial growth and shares no sequence homology with the human ortholog [40]. The down regulated expression of cmK indicates that due the structural similarity of cytidine, 5-azacytidine interferes with DNA synthesis processes.…”
Section: Discussionmentioning
confidence: 98%
“…The cmK gene encodes cytidine kinase that catalyzes the phosphoryl transfer from ATP to cytidine monophosphokinase (CMP) and deoxycytidine monophosphokinase (dCMP), resulting in the formation of nucleotide diphosphates in cellular nucleic acid synthesis. A previous study found that cmK is an essential CMP kinase for bacterial growth and shares no sequence homology with the human ortholog [40]. The down regulated expression of cmK indicates that due the structural similarity of cytidine, 5-azacytidine interferes with DNA synthesis processes.…”
Section: Discussionmentioning
confidence: 98%
“…The slightly favorable entropic contribution is somewhat surprising as it has been reported that ATP binding induces conformational changes in the LID domain of CMKs [14,17]. It is thus tempting to suggest that the favorable overall entropic contribution is due to exclusion of water molecules from MtCMK active site, which should minimize the more favorable intramolecular hydrolysis of ATP to bound ADP and phosphate in the enzyme active site as compared to hydrolysis in solution [38].…”
Section: Thermodynamic Signatures Of Substrate(s) and Product(s) Intementioning
confidence: 99%
“…6), and analysis of MtCMK structural model (Fig. 7) and of other bacterial CMK protein structures [13,14,42] suggest that the chemical groups that may contribute to the proton uptake effect include the 3-imino group of pyrimidine ring (pK a of 4.26), and/or the side chain(s) of Asp134 and Asp187 (Fig. 7) located in the NMP binding site (pK a value of 3.9-4.0 for the b-carboxyl group of aspartate in solution).…”
Section: Ph Dependence Of Mtcmk:nmp Binary Complex Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial cytidylate kinase or cytidine monophosphate kinase (CMP kinase) catalyses the phosphoryl transfer from ATP to CMP and dCMP, resulting in the formation of nucleoside diphosphates. CMP kinase has been shown to be necessary for bacterial growth in Streptococcus pneumoniae [10]. The Staphylococcus aureus CMP kinase crystal structure has been recently resolved [11].…”
Section: Introductionmentioning
confidence: 99%